Substance use patterns associated with recent exposure to fentanyl among people who inject drugs in Vancouver, Canada: A cross-sectional urine toxicology screening study - Hayashi, Kanna (Drug Alcohol Depend, 2017)
INTRODUCTION: Vancouver, Canada is experiencing an opioid overdose crisis where fentanyl, a potent, synthetic opioid contaminating the illicit drug supply, has been detected in the majority of fatal overdose cases. Despite its growing presence throughout North America, few studies have characterized exposure to fentanyl among people who use illicit drugs (PWUD). We sought to identify the prevalence and correlates of fentanyl exposure among PWUD in Vancouver. METHODS: Data were derived from cohort studies of PWUD in Vancouver. In June –October 2016, we administered multi-panel urine drug screens (UDS) to detect recent exposure to fentanyl and eight other substances. Multivariable logistic regression was used to identify substance use patterns associated with recent fentanyl exposure among participants who injected drugs in the past six months (PWID). RESULTS: Among 669 PWUD including 250 (37.4%) females and 452 (67.6%) PWID, 97(14.5%) tested positive for fentanyl. All these individuals also tested positive for other substances, most commonly for morphine/heroin (89.9%), amphetamine/methamphetamine(75.3%) and cocaine (74.2%). A fentanyl detection rate was significantly higher among PWID (19.7%) compared to non-injection drug users (3.9%) (p<0.001). In multivariable analyses, younger age (adjusted odds ratio [AOR]: 0.96) and testing positive for morphine/heroin (AOR: 6.73), buprenorphine (AOR: 4.25), amphetamine/methamphetamine (AOR: 3.26), cocaine (AOR: 2.92) and cannabis (AOR: 0.52) remained independently associated with fentanyl exposure (all p<0.05). CONCLUSION: With one in five PWID being exposed to fentanyl, there is an urgent need to design and scale up interventions to reduce overdose risk, including a range of opioid agonist therapies.